2019
DOI: 10.1111/ctr.13724
|View full text |Cite
|
Sign up to set email alerts
|

Missed opportunities for DCD kidney donors: Evaluation of warm ischemic time and associated functional warm ischemic time

Abstract: Introduction: Many transplant centers utilize a hard cutoff of 2 hours of warm ischemic time (WIT), defined as the time from withdrawal of life-sustaining measures to cold organ flush, to exclude donation after circulatory determination of death (DCD) kidney donation. As a result, almost a quarter of withdrawals to retrieve DCD organs fail to produce kidney transplants in Ontario. In order to assess our ability to increase organ yield, we wanted to characterize WIT and functional WIT (fWIT, time from systolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 15 publications
0
7
1
Order By: Relevance
“…This novel nding differs from previous investigations, which reported a longer duration of functional warm ischemia, de ned as the rst recorded time of systolic BP less than 50 mmHg to cold perfusion, was associated with slow graft function, and premature graft loss in DCD kidneys 15 . Prior work have indicated that a longer agonal time was associated with a signi cantly increased risk of DGF and primary non-function by 50% 16 , particularly in donors where the duration of systolic BP less than 80 mmHg exceeded 20 minutes before cold perfusion, with this effect more apparent in younger donors (aged < 40 years) 5 .…”
Section: Comparison To Previous Studiescontrasting
confidence: 99%
“…This novel nding differs from previous investigations, which reported a longer duration of functional warm ischemia, de ned as the rst recorded time of systolic BP less than 50 mmHg to cold perfusion, was associated with slow graft function, and premature graft loss in DCD kidneys 15 . Prior work have indicated that a longer agonal time was associated with a signi cantly increased risk of DGF and primary non-function by 50% 16 , particularly in donors where the duration of systolic BP less than 80 mmHg exceeded 20 minutes before cold perfusion, with this effect more apparent in younger donors (aged < 40 years) 5 .…”
Section: Comparison To Previous Studiescontrasting
confidence: 99%
“…Recent study, however, demonstrates that the warm ischemic time has significant effects on DCD graft function. 19,20 When offered kidneys, it is important to consider just how dangerous it is to remain on the waitlist, waiting for a kidney. The overall 5-year survival rate for end-stage renal disease patients is 35%.…”
Section: Discussionmentioning
confidence: 99%
“…Around 20% of all potential DCD kidneys were never retrieved because the donor's agonal phase exceeded the 2-h national upper limit set for kidney donation. A Canadian retrospective study showed that 21% of potential DCD donors who did not end up donating due to an agonal phase >2 h did sustain cardiocirculatory arrest between 2 and 4 h after withdrawal of treatment [ 19 ]. The acceptable maximum duration of the agonal phase is still under debate, but several studies support a waiting time of up to 4 h for DCD kidney donation.…”
Section: Discussionmentioning
confidence: 99%